Analysis of the Influence Structure Between Design Factors and Heat Source Equipment Capacity: A Case Study on Office Building Design with a Central Heat Source System in Warm Regions of Japan - Yuta Eto; Koki Kikuta; Yuhei Abe; Takao Sawachi (Buildings)
To achieve carbon neutrality by 2050, the realization of Net-Zero-Energy Buildings (ZEBs) and the proper design of heat source equipment capacity are essential. Consequently, numerous studies have been conducted to prevent overdesign. However, most previous studies have analyzed the factors influencing heat source equipment capacity as independent and isolated variables. In actual design practice, however, factors interact in complex and interdependent ways, yet few studies have considered the interrelationships among these factors or conducted a structural and comprehensive analysis of their influence on heat source equipment capacity. Therefore, this study aims to quantitatively model the influence structure between design factors and heat source equipment capacity using Structural Equation Modeling (SEM), focusing on office buildings with a central heat source system in warm regions of Japan. This research offers a novel perspective not found in previous studies by structurally and comprehensively analyzing the relationship between design factors and heat source equipment capacity, examining the interactions between the factors and their impact on equipment capacity in stages. As a result, by modeling the influence structure, it was confirmed that the diversity factor, handling of internal heat gain, and appropriate design based on actual building usage, such as internal heat gain and the safety factor, are effective for optimizing heat source equipment capacity. Moreover, the result also confirmed that industry, company size, building scale, building use, and software influence the above design factors. This study is a case study that focuses on the maximum heat load calculation in mechanical equipment design and attempts to model the influence of design factors and heat source equipment capacity. However, it is expected that future studies using the same methodology as this study and incorporating additional factors not discussed in this study, and expanding across various regions, will provide a valuable and effective approach to optimizing heat source equipment capacity.